2021
DOI: 10.1051/0004-6361/202141093
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and nature of central molecular outflows in nearby star-forming disk galaxies

Abstract: Central molecular outflows in spiral galaxies are assumed to modulate their host galaxy’s star formation rate (SFR) by removing gas from the inner region of the galaxy. Outflows consisting of different gas phases appear to be a common feature in local galaxies, yet, little is known about the frequency of molecular outflows in main sequence galaxies in the nearby universe. We develop a rigorous set of selection criteria, which allow the reliable identification of outflows in large samples of galaxies. Our crite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 106 publications
1
25
1
Order By: Relevance
“…Our rich multiwavelength measurements have already supported multiple observational studies on PHANGS galaxies. These studies cover a broad range of topics, including the dynamical equilibrium of the ISM (Sun et al 2020b), pressures in H II regions (Barnes et al 2021), morphological features in the stellar disks (Querejeta et al 2021), nuclear gas outflows (Stuber et al 2021), and the molecular gas-star formation cycle (Pan et al 2022). We also expect similar applications in future studies on PHANGS targets examining molecular cloud lifecycle (J.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our rich multiwavelength measurements have already supported multiple observational studies on PHANGS galaxies. These studies cover a broad range of topics, including the dynamical equilibrium of the ISM (Sun et al 2020b), pressures in H II regions (Barnes et al 2021), morphological features in the stellar disks (Querejeta et al 2021), nuclear gas outflows (Stuber et al 2021), and the molecular gas-star formation cycle (Pan et al 2022). We also expect similar applications in future studies on PHANGS targets examining molecular cloud lifecycle (J.…”
Section: Discussionmentioning
confidence: 90%
“…In this way, we assemble the diverse set of observational data described in Section 2 into a coherent, multiwavelength database. An early version of this database was constructed by Sun et al (2020b), with its subsequently improved versions used in several publications (e.g., Herrera et al 2020;Jeffreson et al 2020;Barnes et al 2021;Querejeta et al 2021;Stuber et al 2021). The source code for database construction, including generic tools for aggregating measurements from maps and catalogs into the existing database, is available on GitHub, 45 and a copy of the version used in this article is published on Zenodo (Sun 2022).…”
Section: Cross-spatial-scale Analysismentioning
confidence: 99%
“…Hopkins et al 2006). The PHANGS galaxies have AGN classifications from Véron-Cetty & Véron (2010); Stuber et al (2021), and we checked if these known AGN show different ISM morphologies. Fourteen (24%) of the PHANGS systems included here are are identified as having AGN in Véron-Cetty & Véron (2010), four are classed as Seyfert 1, 6 are Seyfert 2, and 4 are LINERS (two of which also show broad Balmer lines).…”
Section: Agnmentioning
confidence: 99%
“…Thus, galactic cold (neutral atomic and molecular) outflows are important phenomena in galaxy evolution (Veilleux et al 2020). A recent observational study by Stuber et al (2021) suggested that a nonnegligible number of star-forming galaxies (20%-25%) show outflow-like features in carbon monoxide (CO) even at redshift = 0.…”
Section: Introductionmentioning
confidence: 99%